Biodegradable packaging films with ε-polylysine/ZIF-L composites. (15th August 2022) - Zhang, Lei; Wang, Ziyuan; Jiao, Yi; Wang, Zichen; Tang, Xiuming; Du, Zhanxin; Zhang, Zeyang; Lu, Shihai; Qiao, Changsheng; Cui, Jiandong
Abstract: Recent years, biobased polymer packaging film in food packaging has witnessed great developments. However, it is still a challenge to develop biodegradable packaging films with antimicrobial property and mechanical strength. Herein, agar and polyvinyl alcohol (PVA)/Chitosan (CS) packaging films with ε-polylysine/ZIF-L nanocomposites (ε-PL@ZIF-L) were developed for the first time. Due to the incorporation of the nanocomposite, UV/visible light barrier properties (the transmittance decreased by 10.9%) of the films were improved, and the elongation at break of the composite agar films were increased by 43.0%. In the antimicrobial assays, with 4% ε-PL@ZIF-L, the inhibition zone diameters against Bacillus subtilis were 10 times as compared with the pure PVA/CS film. Furthermore, compared with commercial PE film, agar films and PVA/CS films with 4% ε-PL@ZIF-L nanocomposites could provide long-term protection for strawberry to avoid the microbial infection and prolong the shelf life of the fruit at 25 °C. The results suggested that the agar and PVA/CS packaging films with ε-PL@ZIF-L nanocomposites could significantly behave as potent antibacterial material in food packaging and preservation systems. Graphical abstract: Image 1 Highlights: Novel biodegradable packaging films with ε-PL@ZIF-L nanocomposites were prepared. The films with ε-PL@ZIF-L nanocomposites showed enhanced antimicrobial activities than agar film and PVA/CS film. The films with ε-PL@ZIF-L nanocomposites are potential for practical application in food packaging.